Comparison of the Results of Some Stock Market Indices for Listed Corporations Socially Responsible in the World - Sikacz, Hanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The article quoted a data showing the observed trend of the growing importance in the corporate social responsibility. Important from the point of view of that growth was a comparison of the functions performed by the indexes CSR/SRI/ESG on present day. The main purpose of this article is to analyse the behaviour of some of the world stock market indices of socially responsible companies (DJSI World, DJSI North America, FTSE4GOOD Global, MSCI KLD 400 Social, CALVERT Social (CSI), MSCI World ESG, STOXX Europe Sustainability, DJSI Europe). The article also includes a comparative analysis of the results of indexes RESPECT, WIG20, mWIG40 i sWIG80, and also WIG-BANKI, WIG-BUDOW, WIG-CHEMIA, WIG-DEWEL, WIG-ENERG, WIG-INFO, WIG-MEDIA, WIG-PALIWA, WIG-SPOZYW, WIG-SUROWC, WIG-TELKOM. Analysis of the global index was based on data obtained from the Datastream database, the data to the comparison RESPECT Index with other indices came from the databases of Warsaw Stock Exchange and Parkiet The newspaper of the Stock Exchange. The data being presented show that the performance indices (trend) in the chosen periods behave similarly, but their efficiency varies. Not all index's values for two of the examined periods were characterized by growth. The results also show that investments in socially responsible businesses in selected capital markets are not associated with resistance to the collapse of the stock market. Information about the participation of the company in the index is not a guarantee to the investor that the investment in the company in question will bring a reasonable return.